Struggling to Get It Right: Performance Measurement Challenges and Strategies for Addressing Them among Funders of Human Services. Issue 3 (3rd November 2016) - Campbell, David A.; Lambright, Kristina T.
Abstract : This article examines the challenges public and nonprofit human service funders face in the performance measurement process and the strategies they use to address these challenges. We use survey and interview data to compare funders' experiences across a region. Common challenges included dissatisfaction with formal data collection procedures, difficulty getting providers to comply with reporting requirements, provider performance problems, and lack of capacity to use performance information. Capacity issues were a greater concern for smaller funders. Funders used a variety of strategies to address challenges. Use of some strategies depended on context. Practices were relatively consistent across funder groups.